Lysophosphatidylcholine Acyltransferase1 Overexpression Promotes Oral Squamous Cell Carcinoma Progression via Enhanced Biosynthesis of Platelet-Activating Factor - Shida-Sakazume, Tomomi; Endo-Sakamoto, Yosuke; Unozawa, Motoharu; Fukumoto, Chonji; Shimada, Ken; Kasamatsu, Atsushi; Ogawara, Katsunori; Yokoe, Hidetaka; Shiiba, Masashi; Tanzawa, Hideki; Uzawa, Katsuhiro (PloS one, 2015)
The relevance of lysophosphatidylcholine acyltransferase1 (LPCAT1), a cytosolic enzyme in the remodeling pathway of phosphatidylcholine metabolism, in oral squamous cell carcinoma (OSCC) is unknown. We investigated LPCAT1 expression and its functional mechanism in OSCCs. We analyzed LPCAT1 mRNA and protein expression levels in OSCC-derived cell lines. Immunohistochemistry was performed to identify correlations between LPCAT1 expression levels and primary OSCCs clinicopathological status. We established LPCAT1 knockdown models of the OSCC-derived cell lines (SAS, Ca9-22) for functional analysis and examined the association between LPCAT1 expression and the platelet-activating factor (PAF) concentration and PAF-receptor (PAFR) expression. LPCAT1 mRNA and protein were up-regulated significantly (p<0.05) in OSCC-derived cell lines compared with human normal oral keratinocytes. Immunohistochemistry showed significantly (p<0.05) elevated LPCAT1 expression in primary OSCCs compared with normal counterparts and a strong correlation between LPCAT1-positive OSCCs and tumoral size and regional lymph node metastasis. In LPCAT1 knockdown cells, cellular proliferation and invasiveness decreased significantly (p<0.05); cellular migration was inhibited compared with control cells. Down-regulation of LPCAT1 resulted in a decreased intercellular PAF concentration and PAFR expression. LPCAT1 was overexpressed in OSCCs and correlated with cellular invasiveness and migration. LPCAT1 may contribute to tumoral growth and metastasis in oral cancer.